ESTIMATES OF GENETIC VARIABILITY AND HERITABILITY FOR YIELD AND YIELD COMPONENT TRAITS IN MUNGBEAN [VIGNA RADIATA (L.) WILCZEK] - MEHANDI, SUHEL; SINGH, CHANDRA MOHAN; KUSHWAHA, VINOD KUMAR (The Bioscan, 2013)
Mungbean is an important crop to meet the challenges of food and nutritional security due to its nature of high protein and other micronutrients. Seed yield is a dependent trait, whose manifestation depends entirely on the component traits. With this view, the present investigation was undertaken to estimate the genetic parameters on various quantitative traits with 21 mungbean genotypes in randomized block design with three replications during kharif 2010. The results indicated that the traits viz., plant height (95.15, 34.20), number of clusters per plant (95.51, 30.74) and number of pods per plant (99.12, 67.30) exhibited high heritability (>60) coupled with high to moderate genetic advance as percent of mean (>20), which may be improved through simple plant selection methods. While the remaining traits showed high to moderate heritability (30-60) coupled with moderate (10-20) to low (<10) genetic advance as percent of mean, suggesting predominance of non-additive gene action in the expression of the traits, therefore may be potentially utilized in recombination breeding. Furthermore, based on their per se performance, the suitable genotypes for these traits could be isolated and utilize for mungbean improvement.